ANALISIS YURIDIS PERCERAIAN PADA PENGADILAN AGAMA DI NEGARA INDONESIA DAN BRUNEI DARUSSALAM: Juridical Analysis of Divorce in Religious Courts in Indonesia and Brunei Darussalam - Wahyu Saputra; Ning Adiasih (Reformasi Hukum Trisakti, 2024)
There are differences in the settlement of divorce between Indonesia and Brunei Darussalam. The formulation of the problem is the similarities and differences in divorce arrangements according to Indonesian law and Brunei Darussalam law and how the divorce procedure in religious courts and the Sharia Court. The research was conducted normatively, descriptive analysis, sourced secondary data based on Primary and Secondary legal materials, analyzed caulitatively and drew conclusions with deductive logic. The results of the discussion found similarities in the divorce process in the Religious Court and the Sharia Court and differences in Brunei Darussalam allow for divorce to be carried out by the Sharia Court and while in Indonesia it does not regulate divorce outside the court. The conclusion is that broadly speaking the law on divorce in Indonesia and Brunei Darussalam has 2 similarities and 5 differences.